Perfect will theology : divine agency in reformed scholasticism as against Suárez, Episcopius, Descartes, and Spinoza - Bac, J. Martin (Brill's series in church history., 2010)
Reformed Scholasticism, Episcopius, Suarez, Descartes, Spinoza, divine will, Perfect Being Theology, providence, possible worlds.